Public Policy and Rural Education: advances and challenges - Silva, Claudio Rodrigues da; Dal Ri, Neusa Maria [UNESP] (Univ Federal Norte Tocantins-ufnt, 2024)
. The objective of this text is to present an analysis of the trajectory of Rural Education, an educational policy governed by the right to education. The current situation provides the deepening of this debate, because in 2022, the 20th anniversary of the institution of the Operational Guidelines for Basic Education in Rural Schools occurred. But at the same time, there have been attacks on public education and school education modalities involving segments of the population, such as the Rural Education. The procedures used in the investigation were bibliographical and documentary research. It was concluded that the public policy for the Rural Education was an achievement of organizations and social movements in the field. However, in recent years, after the parliamentary coup of 2016, the Rural Education was the target of several attacks, due to the measures implemented by the federal government (2019-2022), which involved setbacks to the right to contextualized education of rural peoples, challenges for this educational modality.
Keywords: social movements and education; educational policies; rural education